2003
DOI: 10.17763/haer.73.1.8465k88616hn4757
|View full text |Cite
|
Sign up to set email alerts
|

Correcting the SAT's Ethnic and Social-Class Bias: A Method for Reestimating SAT Scores

Abstract: The SAT has been shown to be both culturally and statistically biased against African Americans, Hispanic Americans, and Asian Americans. In this article, Roy Freedle argues for a corrective scoring method, the Revised-SAT (R-SAT), to address the nonrandom ethnic test bias patterns found in the SAT. The R-SAT, which scores only the "hard" items on the test, is shown to reduce the mean-score difference between African American and White SAT test-takers by one-third. Further, the R-SAT shows an increase in SAT v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
3
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(153 citation statements)
references
References 3 publications
11
136
3
3
Order By: Relevance
“…Freedle argued it is possible that all students might encounter and understand difficult vocabulary in more uniform ways than they would the highly contextual definitions of the common vocabulary found in easier test items. Freedle's (2003) findings were consistent with those of Fagan and Holland (2002) who found that white and African American students performed similarly on a verbal test of rare words that had just been introduced to students, whereas white students outscored the African American students on a test of vocabulary words that were more likely to have been encountered outside of school. Still, Dorans and Zeller (2004) (Scherbaum & Goldstein, 2008) as well as slightly less convincing evidence that fell somewhere between the arguments of Freedle and Freedle's critics (Santelices & Wilson, 2010).…”
Section: Quantitative Studiessupporting
confidence: 87%
“…Freedle argued it is possible that all students might encounter and understand difficult vocabulary in more uniform ways than they would the highly contextual definitions of the common vocabulary found in easier test items. Freedle's (2003) findings were consistent with those of Fagan and Holland (2002) who found that white and African American students performed similarly on a verbal test of rare words that had just been introduced to students, whereas white students outscored the African American students on a test of vocabulary words that were more likely to have been encountered outside of school. Still, Dorans and Zeller (2004) (Scherbaum & Goldstein, 2008) as well as slightly less convincing evidence that fell somewhere between the arguments of Freedle and Freedle's critics (Santelices & Wilson, 2010).…”
Section: Quantitative Studiessupporting
confidence: 87%
“…For instance, the research that is most recognized and supported within this lens is typically not practitionerdriven and engaged with community partners. Similarly, the SAT has been noted to be biased towards students of color and institutions that serve them are penalized in ranking systems that consider it (Freedle, 2003). The observed and potential implications of these structures and the other tensions described are discussed at length in the following section.…”
Section: Performance-and Prestige-based Fundingmentioning
confidence: 92%
“…It was in the year 2003 when a controversial article by Roy Freedle (2003) was published by Harvard Educational Review. In his research paper Freedle stated the fact that SAT was both culturally and statistically biased, but through his strenuous work he had found a way to reduce disparities in scores.…”
Section: Literature Reviewmentioning
confidence: 99%